The Functional Neuroanatomy of Developmental Dyslexia Across Languages and Writing Systems - Richlan, Fabio (Frontiers in Psychology, 2020)
The present article reviews the literature on the functional neuroanatomy of developmental dyslexia across languages and writing systems. This includes comparisons of alphabetic languages differing in orthographic depth as well as comparisons across alphabetic, syllabic, and logographic writing systems. It provides a synthesis of the evidence for both universal and language-specific effects on dyslexic functional brain activation abnormalities during reading and reading-related tasks. Specifically, universal reading-related underactivation of dyslexic readers relative to typical readers is identified in core regions of the left hemisphere reading network including the occipito-temporal, temporo-parietal, and inferior frontal cortex. Orthography-specific dyslexic brain abnormalities are mainly related to the degree and spatial extent of under- and overactivation clusters. In addition, dyslexic structural gray matter abnormalities across languages and writing systems are analyzed. The neuroimaging findings are linked to the universal and orthography-dependent behavioral manifestations of developmental dyslexia. Finally, the present article provides insights into potential compensatory mechanisms that may support remediation across languages and writing systems.